Peran Media Poster Sebagai Sarana Edukasi Politik Pada Mahasiswa Politik Universiti Malaysia - Syafrudin, Iqbal; Maiwan, Mohammad; Sumadi, Tjipto (Muttaqien Publishing Pusat Penelitian dan Pengabdian kepada Masyarakat STAI DR. KH.EZ. Muttaqien Purwakarta, 2025)
The background of this service is to improve the knowledge and understanding of political students at Universiti Sains Malaysia so that they can have knowledge and understanding of the importance of the role of technology such as poster media in political education. Through the questionnaire that has been given, this service can prove that with the socialization, students can better understand the role of posters as a means of political education both in Indonesia and in Malaysia. Students increasingly understand that many perspectives of society consider the existence and meaning of politics as something positive, and there are also those who consider politics to be something negative. In fact, political science is very important to learn because consciously or not, politics actually influences most of human life in society and the state. Through politics, people's lives depend on the decisions taken in it. For that political education is very necessary, one of which is through posters.